Population dynamics of Phyllocnistis citrella Stainton, 1856 (Lepidoptera, Gracillariidae) and impact of its parasitism on clementine trees at the Boufarik-Blida station (Algeria) - Houda, Bendoumia; Ibtissam, Lorabi; El Houda, Oudjouadj Nour; Hassina, Khechna; Salaheddine, Doumandji (Seven Editora, 2024)
A study was conducted for eight months in 2021 in the Boufarik-Blida region (Algeria) to analyse the population dynamics of Phyllocnistis citrella and the incidence of the parasite on citrus fruit, in particular clementines. The main data showed a significant increase in the rate of parasitism, with peaks of 73% and 72% during the first outing. After 28 June, fluctuations in the rate of parasitism were observed, highlighting the importance of the activity of beneficials, particularly those reared in a greenhouse close to the orchards, such as Semielacher pesiolatus. The relationship between rates of infestation and parasitism is increasing, with parasitism exceeding infestation. This dynamic is influenced by several factors, including temperature variations, and highlights the effectiveness of biological control using parasitoids. The installation of greenhouses for rearing beneficials near infested orchards, combined with other integrated pest management methods, represents a promising and sustainable solution for combating citrus leafminer. DOI:https://doi.org/10.56238/sevened2024.018-050